The Theory of Share Tenancy Revisited–Again - Reid,, Joseph D. (Journal of Political Economy, 1977)
In fact, share-farmed lands yield as much as rented or owner-cultivated lands. In traditional theory, share-farmed lands yield less, for share tenants stint their efforts. This article shows that economists' standard assumptions about a market equilibrium reconcile theory with fact: when contracts are enforced, share farmers labor as diligently as others. Evidence is advanced that gain from the joining of tenant and landlord interests, not gain from the dispersion of agricultural risk, is the impetus to share tenancy.